Brave Hermeneutics, the Eastern Question, and Kingsley’s Hypatia. - Ross, Sarah (Victorian Studies)
This article places Charles Kingsley’s Hypatia (1852–53) within the context of the escalating conflict later to become the Crimean War. Resituating the novel against the backdrop of the Eastern Question circa 1851 allows us to make sense of Kingsley’s scenes of Gothic apathy, manly heroism, and religio-political war more broadly. This essay argues that Kingsley thematizes and stages questions of hermeneutics in order to enter mid-century debates about what constituted good interpretation, and also that the centrality of Jewishness within Hypatia is crucial for the novel’s hermeneutic questions. Victorian Britons must rely, not on Catholic history, but on Anglo-Jews to understand the Bible more fully. Ultimately, Kingsley’s Eastern novel demands that readers use interpretation to realize their ethical duty and become righteous soldiers in the present age.